Rent sharing and the gender bargaining gap: Evidence from the banking sector - Sena Coskun; Hermann Gartner; Ahmet Ali Taskin (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2025)
We use the removal of public bank guarantees in Germany as a quasi-natural experiment to estimate the gender bargaining power gap. Using comprehensive wage data from the universe of banking employees, combined with bank-level financial information, we find that women have approximately two-thirds of the bargaining power of men. Our model-based analysis suggests that this gender bargaining gap alone accounts for 13 to 25 percent of the observed gender wage gap in the sector. These findings highlight an important driver of gender inequality: Changes in firm profitability can reduce the gender wage gap, even without improvements in structural gender equality. This effect has significant implications for high-rent, high-inequality industries such as finance, where rent-sharing mechanisms favor male employees. – – Wir nutzen den Wegfall staatlicher Bankgarantien in Deutschland als quasi-natürliches Experiment, um den Unterschied zwischen Männern und Frauen bei der Verhandlungsmacht abzuschätzen. Anhand umfassender Lohndaten von Bankangestellten, kombiniert mit Finanzinformationen auf Bankebene, stellen wir fest, dass Frauen etwa zwei Drittel der Verhandlungsmacht von Männern haben. Unsere modellbasierte Analyse legt nahe, dass diese geschlechtsspezifische Verhandlungsmacht allein 13 bis 25 Prozent der beobachteten geschlechtsspezifischen Lohnlücke in der Branche ausmacht. Die Ergebnisse zeigen eine wichtige Ursache der Lohnunterschiede zwischen Männern und Frauen: Eine Veränderung der Profitabilität von Firmen kannn die geschlechtsspezifische Lohnlücke verringern, ohne dass sich die Gleichstellung der Geschlechter strukturell verbessert. Dieser Effekt hat erhebliche Auswirkungen auf Branchen mit hohen Profiten und hoher Ungleichheit wie der Finanzbranche, in denen der Modus der Verteilung der Profite männliche Beschäftigte begünstigt.
Keywords: G21; G28; J16; J31; J71; 330; Bank guarantees; rent sharing; gender gap; gender bargaining power gap; bargaining power; gender difference in rent sharing